2016
DOI: 10.4172/2471-8726.1000112
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Importance of Gene and Environment in the Etiology and Prevention of Type 2 Diabetes Mellitus in High-Risk Populations

Abstract: Current literature focuses on the complications and treatment of Type 2 Diabetes Mellitus (T2DM) while clustering environmental and genetic factors to explain the disease. Interventions proposed to reduce diabetes prevalence should focus predominantly on initiating active rapports of family members and promoting a more communicationoriented preventative approach between diabetics and non-diabetics. Due to varying risks in T2DM by race and ethnicity, these populations should follow race-appropriate guidelines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…This had a response rate of 74% in HUNT2 and 53% in HUNT3 (24). At follow-up, participants were interviewed by nurses to confirm their age at diagnosis and details on the time-point of beginning different types of diabetes treatment (16). They provided a fasting blood sample for measurements of glucose, glycosylated hemoglobin (HbA1c), serum C-peptide levels, and antibodies against glutamic acid decarboxylase (GADA) (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This had a response rate of 74% in HUNT2 and 53% in HUNT3 (24). At follow-up, participants were interviewed by nurses to confirm their age at diagnosis and details on the time-point of beginning different types of diabetes treatment (16). They provided a fasting blood sample for measurements of glucose, glycosylated hemoglobin (HbA1c), serum C-peptide levels, and antibodies against glutamic acid decarboxylase (GADA) (27).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a positive association with migraine was found for non-insulin dependent DM (14). Many studies have investigated risk factors and consequences of type 1 DM and type 2 DM (15,16), but very few previous studies have evaluated the relationship between migraine and specific DM subtypes. Two studies found no association between type 2 DM and migraine (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most noticeable components of T2D is the significant variations in disease pathogenesis between ethnicities, which is attributed to complex genetic components and environmental factors (Samsom et al 2016). Despite the fact that environmental factors of sedentary lifestyle, overconsumption of fat/carbohydrate enriched diets, socioeconomic status, and air pollution increase the risk for T2D, it is evident that the genetic background plays a critical role in determining the host response towards these environmental conditions (susceptibility versus resistance).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that 11.6% of Chinese adults had diabetes and 50.1% had prediabetes, a precursor to T2DM [ 1 ]. T2DM is resulted from both genetic and environmental factors [ 2 ].…”
Section: Introductionmentioning
confidence: 99%